The outcome measure of proximal humerus fracture treated by open reduction and internal fixation with proximal humerus internal locking system based on Oxford Shoulder Score - Falsafi, Mani; Altini, Sara; Baghianimoghadam, Behnam; Bahrami-Freiduni, Masoud; Esmaeilnejad-Ganji, Seyed Mohammad Reza; Hajiahmadi, Mahmood; Fallah, Yousef (International Journal of Health Sciences, 2022)
Objective: Proximal humerus fractures became one of the most prevalent upper extremity fractures during recent decades. The use of scoring systems has been taken under consideration to estimate the surveillance, prognosis, and post-operative outcomes. During this study, we investigated the outcome measure of proximal humerus fracture treated by open reduction and internal fixation (ORIF) with plate based on oxford shoulder score (OSS). Furthermore, we tried to propose a new classification system for OSS that could be of prognostic value. Methods: Patients with proximal humerus fracture treated by open reduction enrolled in the study. Persian version of the OSS was completed by the patients. Data were analyzed using SPSS-22. Results: Forty-four patients including 24 women and 20 men were assessed. The mean age was 54.61 (SD ± 19.371) years. The use of a spoon and fork at the same time had the best score and hanging the clothes up in a wardrobe with the operated hand had the worst score in the questionnaire. Comparison of OSS and number of physiotherapy session showed that patients with best outcome had least number of physiotherapy’s session, but it was not statistically significant. Conclusion: OSS is useful to evaluate the function of the traumatized shoulder. We suggest classifying the OSS score into three range groups, good (total score 12–28), moderate (total score 29–44), and bad (total scores 45–60).